AL-ITTIHADIYAH EDUCATION DEVELOPMENT IN NORTH SUMATERA - Mursal Aziz; Muhammad Hasbie Ashshiddiqi (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2020)
This article aims to describe the development of Al-Ittihadiyah education in North Sumatra. The method of this research is manuscript research supported by observations of the development of Al-Ittihadiyah education in North Sumatra. Al-Ittihadiyah is an Islamic-based community organization that has been active in the field of education. Al-Ittihadiyah has a role in the process of renewing Islamic education. One of Al-Ittihadiyah's efforts in uniting Muslims is through education. So in this case Al-Ittihadiyah intends to organize an Islamic education system that is more orderly, more modern, and organized into an organization, especially Islamic schools or colleges that have not been incorporated in a particular organization. The management of Islamic education under the auspices of Al-Ittihadiyah in achieving the ideals of Islamic religious organizations has compiled and formed an Islamic education curriculum according to the needs of Muslims. Al-Ittihadiyah continues to actively participate in organizing Islamic education more regularly and responsively to the needs of the Muslim community. In general, the educational institutions developed by the Al-Ittihadiyah organization are Islamic educational institutions, both in the style of madrassas and religious schools, as well as orphanages from elementary to tertiary levels. Al-Ittihadiyah with various developments continues to be consistent to contribute to the education of the surrounding community. AbstrakArtikel ini bertujuan untuk mendeskripsikan perkembangan pendidikan Al-Ittihadiyah di Sumatera Utara. Adapun metode penelitian ini adalah penelitian naskah dengan didukung observasi perkembangan pendidikan Al-Ittihadiyah di Sumatera Utara. Al-Ittihadiyah merupakan suatu organisasi masyarakat berbasis Islam yang telah memiliki kiprah dalam bidang pendidikan. Al-Ittihadiyah memiliki peran dalam proses pembaharuan pendidikan Islam. Salah satu upaya Al-Ittihadiyah dalam menyatukan umat Islam adalah melalui pendidikan. Maka dalam hal ini Al-Ittihadiyah berkeinginan dalam menyelenggarakan suatu sistem pendidikan Islam yang lebih teratur, lebih modern, dan terorganisir ke dalam suatu organisasi, khususnya sekolah-sekolah atau perguruan perguruan Islam yang belum tergabung dalam suatu organisasi tertentu. Pengelolaan pendidikan Islam dalam naungan Al-Ittihadiyah dalam mencapai cita-cita organisasi keagamaan Islam telah menyusun dan membentuk kurikulum pendidikan Islam sesuai dengan kebutuhan umat Islam. Al-Ittihadiyah terus berpartisipasi aktif dalam menyelenggarakan pendidikan Islam lebih teratur dan responsive terhadap kebutuhan masyarakat Muslim. Secara umum lembaga pendidikan yang dikembangkan organisasi Al-Ittihadiyah adalah lembaga pendidikan Islam, baik bercorak madrasah maupun sekolah-sekolah agama, serta Panti Asuhan mulai tingkat dasar sampai perguruan tinggi. Al-Ittihadiyah dengan berbagai perkembangan terus konsisten untuk berkontibusi dalam pendidikan masyarakat di sekitarnya.